Maximum Waring Ranks of Monomials and Sums of Coprime Monomials. Issue 10 (2nd October 2016) - Holmes, Erik; Plummer, Paul; Siegert, Jeremy; Teitler, Zach
Abstract : We show that monomials and sums of pairwise coprime monomials in four or more variables have Waring rank less than the generic rank, with a short list of exceptions. We asymptotically compare their ranks with the generic rank.